Kobra surgery simulator—a possibility to improve digital teaching? A case-control study - Buchbender, Mayte; Maser, Mathias; Neukam, Friedrich Wilhelm; Kesting, Marco Rainer; Attia, Sameh; Schmitt, Christian (International Journal of Environmental Research and Public Health, 2021)
Computer-aided simulations have long been of great importance in university teaching; however, to date, there is limited use of such simulations in the dental surgical sector. For this purpose, an oral surgery simulator, “Kobra”, was implemented in student training and was evaluated for dental education. Dental students (group 1, third-year and group 2, fourth-year) and dentists of the faculty (control group) were trained to use the simulator. The outcomes for group 1 (apicoectomy of an upper lateral incisor with Kobra), group 2 (removal of an impacted lower wisdom tooth with Kobra) and the control group (both procedures with Kobra) were evaluated. For evaluation purposes, subjective parameters (improvement of practical skills, comparison between conventional training and Kobra simulation, and implementation of simulation-based teaching) and objective parameters (removal of bone, tooth substance and soft tissue measured while performing the Kobra simulation) were assessed using questionnaires with a scale ranging from 1–5. A total of 49 students (third-year n = 29, with 22 women and 7 men; fourth-year n = 20, with 17 women and 3 men) and 10 dentists (women n = 5 and men n = 5) participated. Compared to the Kobra simulation, the conventional training method with plastic models was still favored (the difference was non-significant). Compared to the dentists, the simulation data showed a less precise surgical performance of the students (the difference was not significant). The Kobra simulation may offer an additional method to conventional surgery training using plastic models, with benefits for students and faculty staff.
CRIS-Team Scopus Importer:2021-02-26
Keywords: Coronavirus; COVID-19; Oral surgery; Surgery simulator; Surgical skills